A customizable linearly polarized transmission line based on microstrip spoof surface plasmon polaritons with tilted grooves. Issue 11 (15th November 2020) - Yang, Shaopeng; Xue, Qianzhong; Cai, Yang; Xi, Baokun; Zhang, Lianzheng
Abstract: In this paper, an ultrathin linearly polarized transmission line (TL) based on tilted microstrip spoof surface plasmon polaritons (SSPPs) is proposed. The proposed structure of the TL consists of an ultrathin corrugated metallic strip with periodic tilted groove arrays and metallic ground. Compared with the reported traditional SSPPs, the proposed SSPPs structures with tilted grooves can support the SSPPs wave with a larger propagation constant, which means a stronger field confinement in the microstrip SSPPs structure and effectively lower the dimension in transverse direction of the TL. Besides, the simulation demonstrates that the wave confinement performance can be well maintained when the grooves tilt from 0 to 60°, and the electric field vectors of the tilted grooves undergo a rotation correspondingly, resulting in a flexible polarization. Therefore, the polarization of different angles can be easily realized when the proposed SSPPs is employed as radiating or feeding structure. To verify characteristic of the proposed structure at microwave frequencies, we simulate, fabricate and measure a back‐to‐back transition sample with 45°‐titled grooves. Both simulations and measured results have clearly validated the good characteristic of the proposed designs.